THE EFFECT OF POETRY LEARNING WITH A DEEP LEARNING APPROACH ON THE CRITICAL AND CREATIVE THINKING SKILLS OF GRADE IX STUDENTS AT SMP NEGERI 4 TANAH PUTIH PUTIH - Della Rahmadika; Desi Sukenti (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of poetry learning with a deep learning approach on the critical and creative thinking skills of grade IX students at SMP Negeri 4 Tanah Putih. The study used a quantitative approach with a pseudo-experimental method and a non-equivalent control group design. The research sample amounted to 86 students divided into 43 experimental class students and 43 control class students. The research instruments include learning response questionnaires, implementation observation sheets, poetry analysis description tests, and poetry work assessment rubrics. Data were analyzed through descriptive statistics, reliability tests, normality tests, homogeneity tests, t tests, and MANOVA. The results showed that the average posttest of critical thinking in the experimental class of 81.55 was higher than that of the control class of 69.46 with a t count of 7.376 and significance of 0.000. The average posttest of creative thinking in the experimental class of 78.23 was also higher than that of the control class of 67.72 with a t count of 6.778 and a significance of 0.000. Simultaneous tests showed Wilks' Lambda of 0.477, F of 45.574, and significance of 0.000. Thus, learning poetry with a deep learning approach has a positive and significant effect on students' critical and creative thinking skills.